2015
DOI: 10.2135/cropsci2014.11.0758
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution of Soybean Aphid Biotypes in the United States and Canada during 2008–2010

Abstract: Soybean aphid (Aphis glycines Matsumura) is a native pest of soybean [Glycine max (L.) Merr.] in eastern Asia and was detected on soybeans in North America in 2000. In 2004, the soybean cultivar Dowling was described to be resistant to soybean aphids with the Rag1 gene for resistance. In 2006, a virulent biotype of soybean aphid in Ohio was reported to proliferate on soybeans with the Rag1 gene. The objective was to survey the occurrence of virulent aphid populations on soybean indicator lines across geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
(111 reference statements)
1
29
2
Order By: Relevance
“…For Biotype 2, the value from Cooper et al (2015) is >10 SE higher than the mean observed in this study. For Biotype 2, the value from Cooper et al (2015) is >10 SE higher than the mean observed in this study.…”
Section: Choice Testscontrasting
confidence: 78%
See 4 more Smart Citations
“…For Biotype 2, the value from Cooper et al (2015) is >10 SE higher than the mean observed in this study. For Biotype 2, the value from Cooper et al (2015) is >10 SE higher than the mean observed in this study.…”
Section: Choice Testscontrasting
confidence: 78%
“…We determined that two isolates collected in 2013 consisted of two biotypes. Ranges for asymptotic SEs were 0.06 to 0.09 (Biotype 1), 0.04 to 0.05 (Biotype 2), 0.06 to 0.09 (Biotype 3), and 0.03 to 0.06 (Biotype 4) across the 3 yr. Cooper et al (2015) reported frequencies of 0.21, 0.54, 0.18, and 0.07 from samples taken in similar state geographic areas in 2008 through 2010. A c 2 test (8.0, Pr < 0.24, df = 6) and Fisher's exact test (Pr < 0.26, table P < 0.0001,) performed on Table 1 both showed that the probability of the frequency distributions across the four biotypes being the same for all 3 yr is high.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations